EXPLORING ETHANOL EXTRACT OF KERSEN FRUIT (MUNTINGIA CALABURA L) AS ANTIMICROBIAL AND ANTIBIOFILM - Firmanda, Hafidz; Widodo, Agung Dwi Wahyu; Wahyunitisari, Manik Retno (Folia Medica Indonesiana, 2025)
Infections caused by microbial biofilms pose a clinical treat in terms of patient morbidity and mortality rates. For potential treatment this study aims to determine antimicrobial and antibiofilm activity of kersen fruit extract (Muntingia calabura L) on Staphylococcus aureus, Escherichia coli, and Candida albicans. This research used true experimental method with posttest only control group design. Using 6 kersen fruit extract concentration and 4 replications. Antimicrobial test used tube dilution method and antibiofilm test used two different scenario, biofilm growth inhibition test and biofilm degradation test. MIC result against Staphylococcus aures and Escherichia coli at extract concentration of 6.25% and Candida albicans at concentration 12.5%. MBC result against Staphylococcus aures and Escherichia coli at extract concentration of 12.5% and Candida albicans at concentration 25%. Biofilm growth inhibition test found that kersen fruit extract was able to inhibit biofilm growth of Staphylococcus aures, highest inhibition value at 76.3% and Escherichia coli highest inhibition percentage at 18.18%. Biofilm degradation test showed that kersen fruit extract was able to degrade biofilm of Staphylococcus aures highest degradation value is 26.5%. Kersen fruit extract was shown has antimicrobial activity as bacteriostatic and bactericidal against these microbes. Antibiofilm activity of kersen fruit extract obtained good result at preventing biofilm growth against Staphylococcus aures, while against Escherichia coli obtained weak growth inhibition. In biofilm degradation test, Kersen fruit extract was able to degrade biofilm from Staphylococcus aures with moderate strength.